Ethical Issues in mHealth Research Involving Persons Living with HIV/AIDS and Substance Abuse. (19th September 2013) - Labrique, Alain B.; Kirk, Gregory D.; Westergaard, Ryan P.; Merritt, Maria W.
Abstract : We aim to raise awareness and stimulate dialogue among investigators and research ethics committees regarding ethical issues that arise specifically in the design and conduct of mHealth research involving persons living with HIV/AIDS and substance abuse. Following a brief background discussion of mHealth research in general, we offer a case example to illustrate the characteristics of mHealth research involving people living with HIV/AIDS and substance abuse. With reference to a well-established systematic general ethical framework for biomedical research with human participants, we identify a range of ethical issues that have particular salience for the protection of participants in mHealth research on HIV/AIDS and substance abuse.